Assessment of Variation in Clinical Presentation of Visceral Leishmaniasis Among Patients Attending the Tropical Diseases Teaching Hospital in Sudan - Hammam Abdalrhman Altom Mohammed Ahmed; Ahmed Ali Ahmed Musa; Ahmed Mahmoud; Sayed Sayedahmed; Shiraz Bashir Jabralseed Mohammed; Ehssan Farouk Mohamed Ahmed; Anas Badreldeen Elageb Mohamed; Abdelsalam Mohamed Ahmed Nail (Sudan Journal of Medical Sciences, 2022)
Abstract Background: Visceral leishmaniasis (also known as Kala-azar) is a systemic parasitic infection with many clinical presentations. The present study assesses the variation in presentations among patients who attended the Tropical Diseases Teaching Hospital (TDTH) in Khartoum, Sudan. Methods: This analytical cross-sectional, hospital-based study was conducted at the TDTH between November 2019 and September 2020. Medical records of patients who presented at the TDTH were reviewed using a structured data extraction checklist. The Chi-square test was used to determine the associations between sociodemographic and clinical presentations of patients. P-value < 0.05 was considered as statistically significant. Results: Out of 195 patients,79.5% were male and 48.2% were < 31 years old. Fever was the main clinical presentation (90.2%) while 53.3% presented with weight loss and 72.3% and 39% presented, respectively, with splenomegaly and hepatomegaly. HIV was detected in 4.6% of the patients. RK39 was the main diagnostic test. We found a significant association between the abdominal distention and the age of the patients (P < 0.05) – age groups 11–20 and 41–50 years were more likely to present with abdominal distention than other age groups. Conclusion: There is no exact clinical presentation or routine laboratory findings that are pathognomonic for visceral leishmaniasis; therefore, it should be considered in the differential diagnosis of any patient with fever, weight loss, and abdominal distention, and among patients with HIV.